Echoes of the Holocaust : historical cultures in contemporary Europe - Karlsson, Klas-Göran 1955- Hrsg; Zander, Ulf 1965- (Nordic Acad. Press, 2003)
This book is the first collection of reports from "The Holocaust and European Historical Cultur". The title of the second collection is "Holocaust heritage"